Genetic diversity and structure of the 4th cycle breeding population of Chinese fir (Cunninghamia lanceolata (lamb.) hook) - Jing, Yonglian; Bian, Liming; Zhang, Xuefeng; Zhao, Benwen; Zheng, Renhua; Su, Shunde; Ye, Daiquan; Zheng, Xueyan; El-Kassaby, Yousry A.; Shi, Jisen (Frontiers in Plant Science, 2023)
Studying population genetic structure and diversity is crucial for the marker-assisted selection and breeding of coniferous tree species. In this study, using RAD-seq technology, we developed 343,644 high-quality single nucleotide polymorphism (SNP) markers to resolve the genetic diversity and population genetic structure of 233 Chinese fir selected individuals from the 4th cycle breeding program, representing different breeding generations and provenances. The genetic diversity of the 4th cycle breeding population was high with nucleotide diversity (Pi) of 0.003, and Ho and He of 0.215 and 0.233, respectively, indicating that the breeding population has a broad genetic base. The genetic differentiation level between the different breeding generations and different provenances was low (Fst < 0.05), with population structure analysis results dividing the 233 individuals into four subgroups. Each subgroup has a mixed branch with interpenetration and weak population structure, which might be related to breeding rather than provenance, with aggregation from the same source only being in the local branches. Our results provide a reference for further research on the marker-assisted selective breeding of Chinese fir and other coniferous trees.